1987
DOI: 10.2337/diab.36.8.959
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Suppresses Its Own Secretion In Vivo

Abstract: This study addressed the controversial question of whether a negative-insulin-feedback loop exists in vivo. We utilized prehepatic insulin production, calculated by computerized deconvolution analysis of peripheral C-peptide concentration, as a measure of endogenous insulin secretion. Prehepatic insulin production was determined in 10 normal men who randomly underwent a control study and two additional studies involving different insulin infusion rates that achieved circulating insulin concentrations within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(24 citation statements)
references
References 21 publications
2
21
1
Order By: Relevance
“…In healthy volunteers, exogenous insulin administration suppressed c-peptide release during normoglycemia [12, 13]. This suppressive effect was, however, attenuated during mild hyperglycemia in subjects with non-insulin dependent diabetes [14].…”
Section: Discussionmentioning
confidence: 99%
“…In healthy volunteers, exogenous insulin administration suppressed c-peptide release during normoglycemia [12, 13]. This suppressive effect was, however, attenuated during mild hyperglycemia in subjects with non-insulin dependent diabetes [14].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, early intensive insulin therapy with multiple injections or continuous subcutaneous insulin infusion in subjects with newly diagnosed T2DM has favorable outcomes in terms of recovery and maintenance of beta cell function (especially restoration of acute insulin response) (91). The exact mechanisms behind the beneficial effects of exogenous insulin administration on beta cells are not completely elucidated, but it is though that it allows cells rest, at least in part by down-regulating their metabolism and/or by releasing them from the hyperglycemic stress (92). Insulin therapy may also protect pancreatic beta cells by decreasing the severity of insulitis, suppressing the inflammatory processes, reducing antigen expression and subsequent amelioration of T cell responses/number of infiltrative cells in the islets (93).…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…Hence, the effect of dialysis on u en cannot be defined patient-specifically by the model without added data that was not available in this study. Alternatively, it has been reported that endogenous insulin secretion is also affected by exogenous insulin [38]. As plasma insulin levels are suspected to decrease during dialysis, it is suspected that endogenous insulin secretion would increase at a cohort level.…”
Section: Discussionmentioning
confidence: 99%